Ka-band light-weight high-strength wave-absorbing patch and preparation method thereof
By using a combination of low-density plastic matrix, modified conductive absorber and coupling agent in the Ka-band wave absorber, combined with the refining-refining-refining process and five-roll calendering machine molding, the problems of the absorbing patch in high strength, easy processing, thickness sensitivity and performance stability are solved, and the efficient electromagnetic wave absorption performance and the characteristics of easy mass production are achieved.
Patent Information
- Application Number
- CN202411729283.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing Ka-band wave absorbing patches have difficulties in taking into account high strength and easy processing, thickness sensitivity and performance stability, especially in the uneven mixing of the conductive absorbent and the resin matrix leads to unstable performance.
Low-density non-polar plastics and polar plastics are used as substrates, and surface modification is carried out by combining conductive absorbers with high wave absorption properties (such as conductive carbon black and graphene) and coupling agent. Through the calendering-refining-refining process and five-roll calendering machine calendering, the dispersion uniformity of the electric absorber and the thickness accuracy of the wave absorption patch are improved.
It realizes that the Ka-band wave absorbing patch has excellent electromagnetic wave absorption performance under thin thickness, and has the characteristics of lightweight, high strength, stable quality and easy mass production, and is suitable for different electromagnetic wave absorption occasions.
Smart Images

Figure CN119552440A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of absorbing materials, and in particular to a Ka-band lightweight and high-strength absorbing patch and a preparation method thereof. Background Art
[0002] With the advent of commercial spaceflight, satellite frequency resources are becoming increasingly scarce, and users are increasingly demanding bandwidth and speed for data transmission. The Ka band has begun to enter people's field of vision. The Ka band is a band in the electromagnetic spectrum with a frequency range of 26.5 to 40 GHz. Its communication bandwidth far exceeds that of the C, X, Ku and other bands, and it has great economic value.
[0003] However, due to the characteristics of the Ka-band's short wavelength (8mm) and "resonant absorption", there are currently three major technical difficulties in the mass production of Ka-band absorbing patches: first, it is difficult for absorbing patches to achieve both high strength and easy processing; second, the absorbing performance is highly sensitive to thickness; third, the conductive absorber is not evenly mixed in the resin matrix, resulting in unstable performance.
[0004] Therefore, there is an urgent need to provide an absorbing patch that has good absorption performance in the Ka band and is light, strong, stable in quality, and easy to mass produce. Summary of the invention
[0005] In view of one or more technical problems existing in the prior art, the present invention provides a Ka-band lightweight and high-strength absorbing patch and a preparation method thereof. The absorbing patch provided by the present invention has good absorption performance in the Ka-band, and has the characteristics of light weight, high strength, stable quality, and easy mass production. It can be applied to different electromagnetic wave absorption occasions and has broad application prospects.
[0006] The present invention provides a Ka-band lightweight and high-strength absorbing patch in the first aspect, which comprises plastic particles, a modified conductive absorber, stearic acid and an additive; the plastic particles comprise polar plastic particles and non-polar plastic particles; the modified conductive absorber is a conductive absorber modified by a coupling agent; the conductive absorber comprises conductive carbon black and graphene.
[0007] Preferably, the polar plastic particles account for 30-40% of the mass of the plastic particles;
[0008] The amount of the conductive absorbent is 20-25% of the mass of the plastic particles;
[0009] The amount of stearic acid used is 1-3% of the mass of the plastic particles; and / or
[0010] The graphene accounts for 10% to 15% of the mass of the conductive absorbent.
[0011] Preferably, the polar plastic particles include one or more of polyvinyl chloride, polyethylene terephthalate, and ethylene vinyl acetate; and / or
[0012] The non-polar plastic particles include one or more of polyethylene, polypropylene, and polystyrene; preferably, the density of the non-polar plastic particles is 0.9 to 1.0 g / cm 3 .
[0013] Preferably, the amount of the coupling agent is 1-10% of the mass of the conductive absorbent; preferably, the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
[0014] Preferably, the dosage of the auxiliary agent is 0.5-1% of the mass of the plastic particles; preferably, the auxiliary agent is one or more of a mildew preventer, an anti-aging agent, an antibacterial agent, and an antioxidant.
[0015] Preferably, the particle size of the conductive carbon black is 10 to 50 nm, and the iodine adsorption value is 900 to 1500 mg / g; and / or
[0016] The graphene is multilayer graphene; preferably, the number of layers of the multilayer graphene is 2 to 3.
[0017] In a second aspect, the present invention provides a method for preparing the Ka-band lightweight and high-strength absorbing patch according to the first aspect, the preparation method comprising:
[0018] The plastic particles, stearic acid, modified conductive absorbent and additives are mixed, and after a first banburying, an open banburying and a second banburying are performed to obtain a banburying mixture;
[0019] The kneaded mixture is calendered by a five-roll calender to obtain a Ka-band lightweight and high-strength absorbing patch.
[0020] Preferably, the temperature of the first banburying is 100-150°C and the time is 60-80min;
[0021] The temperature of the open refining is 100-150°C and the time is 5-10 minutes; and / or
[0022] The temperature of the second internal kneading is 100-150° C., and the time is 10-30 minutes.
[0023] Preferably, the speed of the internal mixer during the first internal mixing and the second internal mixing is 40-50 rpm / s;
[0024] The linear speed of the mixing mill during the mixing process is 4 to 6 m / min; and / or
[0025] During the calendering process, the roller speed of the calender is 1 to 1.5 m / min.
[0026] Preferably, the five-roll calender comprises a first roller, a second roller, a third roller, a fourth roller and a fifth roller which are arranged in sequence from front to back;
[0027] The roller temperature of the first roller is 140-150°C; the roller temperature of the second roller is 100-110°C; the roller temperature of the third roller is 100-110°C; the roller temperature of the fourth roller is 70-80°C; the roller temperature of the fifth roller is 40-50°C;
[0028] The gap between the first roller and the second roller is 0.6-0.7 mm; the gap between the second roller and the third roller is 0.42-0.48 mm; the gap between the third roller and the fourth roller is 0.35-0.40 mm; the gap between the fourth roller and the fifth roller is 0.30-0.35 mm.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] The absorbing patch provided by the present invention adopts low-density non-polar plastic and polar plastic as the matrix to improve the processability and peeling strength of the absorbing patch. A conductive absorber (conductive carbon black and graphene) with high absorbing performance is used to achieve low filling of the absorber, so that the absorbing patch has excellent electromagnetic wave absorption performance at a thinner thickness. A coupling agent is used to modify the surface of the conductive absorber to improve the compatibility of the absorber. The compatibility of the electrical absorber is improved by modifying the surface of the conductive absorber. The absorbing patch provided by the present invention has good absorption performance in the Ka band, and has the characteristics of light weight, high strength, stable quality, and easy mass production. It can be applied to different electromagnetic wave absorption occasions and has broad application prospects.
[0031] The present invention improves the uniformity of dispersion of the electric absorber in the resin matrix by adopting the process of internal mixing-open mixing-internal mixing, and improves the accuracy of the thickness of the absorbing patch by adopting the calendering molding method of a five-roll calender, thereby improving the stability of the product. The obtained absorbing patch has high thickness accuracy, good product stability, high strength, easy processing, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1This is a flow chart for preparing the Ka-band lightweight and high-strength absorbing patch provided by the present invention;
[0034] Figure 2 This is a physical picture of the Ka-band lightweight and high-strength absorbing patch provided by the present invention;
[0035] Figure 3 is a reflectivity curve diagram of the Ka-band lightweight high-strength absorbing patch provided in Example 1 of the present invention;
[0036] Figure 4 is a reflectivity curve diagram of the Ka-band lightweight high-strength absorbing patch provided in Example 2 of the present invention;
[0037] Figure 5 This is a reflectivity curve diagram of the Ka-band lightweight and high-strength absorbing patch provided in Example 3 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] The present invention provides a Ka-band lightweight and high-strength absorbing patch in the first aspect, which comprises plastic particles, a modified conductive absorber, stearic acid and an additive; the plastic particles comprise polar plastic particles and non-polar plastic particles; the modified conductive absorber is a conductive absorber modified by a coupling agent; the conductive absorber comprises conductive carbon black and graphene.
[0040] The absorbing patch provided by the present invention adopts low-density non-polar plastic and polar plastic as the matrix to improve the processability and peel strength of the absorbing patch. A conductive absorber with high absorbing performance (conductive carbon black and graphene) is used to achieve low filling of the absorber, so that the absorbing patch has excellent electromagnetic wave absorption performance at a thinner thickness. A coupling agent is used to modify the surface of the conductive absorber to improve the compatibility of the absorber. The compatibility of the electrical absorber is improved by modifying the surface of the conductive absorber. The absorbing patch provided by the present invention has good absorption performance in the Ka band (the reflectivity peak value in the Ka band is ≤-25dB, and the reflectivity mean is ≤-10dB), and is lightweight (surface density ≤400g / m 2 ), high strength (tensile strength ≥ 10MPa, peel strength ≥ 30N / cm), stable quality, and easy mass production. It can be used in different electromagnetic wave absorption occasions and has broad application prospects.
[0041] According to some preferred embodiments, the polar plastic particles account for 30-40% of the mass of the plastic particles (for example, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%); the polar plastic particles or non-polar plastic particles used alone in the present invention cannot be calendered. If the proportion of polar plastic particles is too large, calendering is also impossible.
[0042] According to some preferred embodiments, the amount of the conductive absorbent is 20-25% (for example, 20%, 21%, 22%, 23%, 24% or 25%) of the mass of the plastic particles.
[0043] According to some preferred embodiments, the amount of stearic acid used is 1-3% (for example, 1%, 2% or 3%) of the mass of the plastic particles.
[0044] According to some preferred embodiments, the graphene accounts for 10% to 15% (for example, 10%, 11%, 12%, 13%, 14% or 15%) of the mass of the conductive absorber.
[0045] The present invention cannot form graphene powder by mixing alone, and the mechanical properties (peeling strength and tensile strength) and absorbing performance of the absorbing patch made by using conductive carbon black alone are deteriorated.
[0046] According to some preferred embodiments, the polar plastic particles include one or more of polyvinyl chloride (PVC), polyethylene terephthalate (PET), and ethylene vinyl acetate (EVA); and / or
[0047] The non-polar plastic particles include one or more of polyethylene (PE), polypropylene (PP), and polystyrene (PS); preferably, the density of the non-polar plastic particles is 0.9 to 1.0 g / cm 3 .
[0048] According to some preferred embodiments, the coupling agent is used in an amount of 1 to 10% of the mass of the conductive absorber (for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%); preferably, the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
[0049] According to some preferred embodiments, the dosage of the auxiliary agent is 0.5-1% (for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%) of the mass of the plastic particles; preferably, the auxiliary agent is one or more of an antifungal agent, an anti-aging agent, an antibacterial agent, and an antioxidant.
[0050] According to some preferred embodiments, the particle size of the conductive carbon black is 10 to 50 nm (for example, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm), and the iodine adsorption value is 900 to 1500 mg / g (for example, 900 mg / g, 1000 mg / g, 1100 mg / g, 1200 mg / g, 1300 mg / g, 1400 mg / g or 1500 mg / g). The inventors found that when the particle size of the conductive carbon black is too large and the iodine adsorption value is too small, the mechanical properties (peel strength and tensile strength) and absorbing properties of the obtained absorbing patch are deteriorated.
[0051] According to some preferred embodiments, the graphene is multilayer graphene; preferably, the number of layers of the multilayer graphene is 2 to 3. The inventors found that the mechanical properties (peel strength and tensile strength) and absorbing performance of the absorbing patch made with too many graphene layers deteriorate.
[0052] According to some preferred embodiments, the thickness of the prepared absorbing patch is 0.35-0.40 mm.
[0053] In a second aspect, the present invention provides a method for preparing the Ka-band lightweight and high-strength absorbing patch according to the first aspect, the preparation method comprising:
[0054] The plastic particles, stearic acid, modified conductive absorbent and additives are mixed, and after a first banburying, an open banburying and a second banburying are performed to obtain a banburying mixture;
[0055] The kneaded mixture is calendered by a five-roll calender to obtain a Ka-band lightweight and high-strength absorbing patch.
[0056] The present invention improves the uniformity of dispersion of the electric absorber in the resin matrix by adopting the process of internal mixing-open mixing-internal mixing, and improves the accuracy of the thickness of the absorbing patch by adopting the calendering molding method of a five-roll calender, thereby improving the stability of the product. The obtained absorbing patch has high thickness accuracy, good product stability, high strength, easy processing, and can be mass-produced.
[0057] According to some preferred embodiments, the temperature of the first banburying is 100-150° C. (for example, 100° C., 110° C., 120° C., 130° C., 140° C. or 150° C.), and the time is 60-80 min (for example, 60 min, 65 min, 70 min, 75 min or 80 min);
[0058] The refining temperature is 100-150° C. (for example, 100° C., 110° C., 120° C., 130° C., 140° C. or 150° C.) and the refining time is 5-10 min (for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min); and / or
[0059] The second kneading is performed at a temperature of 100 to 150° C. (for example, 100° C., 110° C., 120° C., 130° C., 140° C. or 150° C.) and for a time of 10 to 30 min (for example, 10 min, 15 min, 20 min, 25 min or 30 min).
[0060] According to some preferred embodiments, the speed of the internal mixer during the first internal mixing and the second internal mixing is 40 to 50 rpm / s (for example, 40 rpm / s, 42 rpm / s, 44 rpm / s, 45 rpm / s, 46 rpm / s, 48 rpm / s or 50 rpm / s);
[0061] The linear speed of the open mill during the open milling process is 4 to 6 m / min (for example, 4 m / min, 4.5 m / min, 5 m / min, 5.5 m / min or 6 m / min); and / or
[0062] During the calendering process, the roller speed of the calender is 1 to 1.5 m / min (for example, 1 m / min, 1.1 m / min, 1.2 m / min, 1.3 m / min, 1.4 m / min or 1.5 m / min).
[0063] According to some preferred embodiments, the five-roll calender includes a first roller, a second roller, a third roller, a fourth roller and a fifth roller arranged in sequence from front to back;
[0064] The roller temperature of the first roller is 140-150°C; the roller temperature of the second roller is 100-110°C; the roller temperature of the third roller is 100-110°C; the roller temperature of the fourth roller is 70-80°C; the roller temperature of the fifth roller is 40-50°C;
[0065] The gap between the first roller and the second roller is 0.6-0.7 mm; the gap between the second roller and the third roller is 0.42-0.48 mm; the gap between the third roller and the fourth roller is 0.35-0.40 mm; the gap between the fourth roller and the fifth roller is 0.30-0.35 mm.
[0066] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.
[0067] Example 1
[0068] S1. Modification of the conductive absorbent: Graphene powder (the number of graphene layers is 2) and conductive carbon black powder (particle size is 10nm, iodine adsorption value is 1500mg / g) are mixed in a mass ratio of 10:90 to obtain a conductive absorbent; the conductive absorbent and a coupling agent (silane coupling agent Si69) are mixed in a ziplock bag, stirred, rubbed and turned over to obtain a modified conductive absorbent; wherein the amount of the conductive absorbent is 20% of the mass of the plastic particles; the amount of the coupling agent is 1% of the mass of the conductive absorbent.
[0069] S2. Internal and open mixing of raw materials: The working temperature of the internal mixer and the open mixer is set to 100°C, the speed of the internal mixer is set to 40rpm / s, and the linear speed of the open mixer is set to 4m / min. Plastic particles (mixed by polyvinyl chloride PVC plastic particles and polyethylene PE plastic particles in a mass ratio of 30:70), stearic acid (the amount of stearic acid is 1% of the mass of the plastic particles), modified conductive absorbent and auxiliary agents (auxiliary agents include mildew inhibitors and antibacterial agents, and the amount of auxiliary agents is 0.5% of the mass of the plastic particles) are added to the internal mixer in sequence, and the first internal mixing is carried out for 60 minutes, and then the open mixing is carried out in the open mixer for 5 minutes, and then the second internal mixing is carried out in the internal mixer for 10 minutes.
[0070] S3. Place the mixture obtained in step S2 in a five-roll calender, set the roller temperatures of rollers A and B of the five-roll calender to 140°C, the roller temperature of roller C to 100°C, the roller temperature of roller D to 70°C, and the roller temperature of roller E to 40°C; set the gap between rollers A and B to 0.7mm, the gap between rollers B and C to 0.48mm, the gap between rollers C and D to 0.40mm, the gap between rollers D and E to 0.35mm, set the roller speed to 1m / min, and perform calendering to obtain a Ka-band lightweight and high-strength absorbing patch.
[0071] Example 2
[0072] S1. Modification of the conductive absorbent: Graphene powder (the number of graphene layers is 2) and conductive carbon black powder (particle size is 30nm, iodine adsorption value is 1200mg / g) are mixed in a mass ratio of 12:88 to obtain a conductive absorbent; the conductive absorbent and a coupling agent (titanium ester coupling agent FT311) are mixed in a ziplock bag, stirred, rubbed and turned over to obtain a modified conductive absorbent; wherein the amount of the conductive absorbent is 22% of the mass of the plastic particles; the amount of the coupling agent is 5% of the mass of the conductive absorbent.
[0073] S2. Internal mixing and open mixing of raw materials: The working temperature of the internal mixer and the open mixer equipment is set to 125°C, the internal mixer speed is set to 45rpm / s, and the open mixer line speed is set to 5m / min. Plastic particles (mixed by polyethylene terephthalate (PET) plastic particles and polypropylene (PP) plastic particles in a mass ratio of 35:65), stearic acid (the amount of stearic acid is 2% of the mass of the plastic particles), modified conductive absorbent and auxiliary agents (auxiliary agents include mildew inhibitors and antibacterial agents, and the amount of auxiliary agents is 0.8% of the mass of the plastic particles) are added to the internal mixer in sequence, and the first internal mixing is carried out for 70 minutes, and then the open mixing is carried out in the open mixer for 8 minutes, and then the second internal mixing is carried out in the internal mixer for 20 minutes.
[0074] S3. Place the mixture obtained in step S2 in a five-roll calender, set the roller temperatures of rollers A and B of the five-roll calender to 145°C, the roller temperature of roller C to 105°C, the roller temperature of roller D to 75°C, and the roller temperature of roller E to 45°C; set the gap between rollers A and B to 0.65mm, the gap between rollers B and C to 0.45mm, the gap between rollers C and D to 0.38mm, the gap between rollers D and E to 0.32mm, set the roller speed to 1.2m / min, and perform calendering to obtain a Ka-band lightweight and high-strength absorbing patch.
[0075] Example 3
[0076] S1. Modification of the conductive absorbent: Graphene powder (the number of graphene layers is 3) and conductive carbon black powder (particle size is 50nm, iodine adsorption value is 900mg / g) are mixed in a mass ratio of 15:85 to obtain a conductive absorbent; the conductive absorbent and a coupling agent (silane coupling agent KH560) are mixed in a ziplock bag, stirred, rubbed and turned over to obtain a modified conductive absorbent; wherein the amount of the conductive absorbent is 25% of the mass of the plastic particles; the amount of the coupling agent is 10% of the mass of the conductive absorbent.
[0077] S2. Internal mixing and open mixing of raw materials: The working temperature of the internal mixer and the open mixing mill equipment is set to 150°C, the internal mixer speed is set to 50rpm / s, and the open mixing mill line speed is set to 6m / min. Plastic particles (obtained by mixing ethylene-vinyl acetate EVA plastic particles and polystyrene PS plastic particles in a ratio of 40:60), stearic acid (the amount of stearic acid is 3% of the mass of the plastic particles), modified conductive absorbent and auxiliary agents (auxiliary agents include mildew inhibitors and antibacterial agents, and the amount of auxiliary agents is 1% of the mass of the plastic particles) are added to the internal mixer in sequence, and the first internal mixing is carried out for 80 minutes, and then the open mixing is carried out in the open mixing mill for 10 minutes, and then the second internal mixing is carried out in the internal mixer for 30 minutes.
[0078] S3. Place the mixture obtained in step S2 in a five-roll calender, set the roller temperatures of rollers A and B of the five-roll calender to 150°C, the roller temperature of roller C to 110°C, the roller temperature of roller D to 80°C, and the roller temperature of roller E to 50°C; set the gap between rollers A and B to 0.6mm, the gap between rollers B and C to 0.42mm, the gap between rollers C and D to 0.35mm, the gap between rollers D and E to 0.30mm, set the roller speed to 1.5m / min, and perform calendering to obtain a Ka-band lightweight and high-strength absorbing patch.
[0079] Comparative Example 1
[0080] The method is basically the same as Example 2, except that in step S2, the plastic particles are polyethylene terephthalate (PET) plastic particles.
[0081] Comparative Example 2
[0082] It is basically the same as Example 2, except that in step S2, the plastic particles are polypropylene (PP) plastic particles.
[0083] Comparative Example 3
[0084] It is basically the same as Example 2, except that: in step S2, the mass ratio of polyethylene terephthalate (PET) plastic particles and polypropylene (PP) plastic particles in the plastic particles is 50:50, that is, polyethylene terephthalate (PET) and polypropylene (PP) plastic particles each account for 50% of the mass of the plastic particles.
[0085] Comparative Example 4
[0086] It is basically the same as Example 2, except that in step S1, the conductive absorber is graphene powder.
[0087] Comparative Example 5
[0088] It is basically the same as Example 2, except that in step S1, the conductive absorbent is conductive carbon black.
[0089] Comparative Example 6
[0090] It is basically the same as Example 2, except that in step S1, the number of graphene layers is 6.
[0091] Comparative Example 7
[0092] It is basically the same as Example 2, except that in step S1, the particle size of the conductive carbon black is 200 nm, and the iodine adsorption value is 200 mg / g.
[0093] Comparative Example 8
[0094] It is basically the same as Example 2, except that: in step S1, the amount of coupling agent (silane coupling agent KH560) is 20% of the mass of the conductive absorbent; the amount of conductive absorbent is 30% of the mass of the plastic particles;
[0095] In step S2, the amount of stearic acid used is 5% of the mass of the plastic particles, and the amount of the auxiliary agent (including mildew inhibitors and antibacterial agents) used is 2% of the mass of the plastic particles.
[0096] Comparative Example 9
[0097] It is basically the same as Example 2, except that: in step S1, the conductive absorbent and the coupling agent are mixed in a ziplock bag without stirring, rubbing or overturning to obtain a modified conductive absorbent.
[0098] Comparative Example 10
[0099] It is basically the same as Example 2, except that: in step S2, the operating temperature of the internal mixer and the open mixer is set to 150°C, the rotation speed of the internal mixer is set to 70rpm / s, and the linear speed of the open mixer is set to 10m / min.
[0100] Comparative Example 11
[0101] It is basically the same as Example 2, except that in step S2, the order of adding materials is: modified conductive absorbent, auxiliary agent, stearic acid and plastic particles.
[0102] Comparative Example 12
[0103] The method is basically the same as Example 2, except that in step S2, no open mixing is performed after the first internal mixing.
[0104] Comparative Example 13
[0105] The method is basically the same as that of Example 2, except that in step S2, the second mixing is not performed.
[0106] Comparative Example 14
[0107] It is basically the same as Example 2, except that: in step S3, a two-roll calender is selected for calendering, wherein the roller temperatures of rollers A and B are set to 145°C, the roller gap is set to 0.65mm, and the roller speed is set to 1.2m / min.
[0108] Comparative Example 15
[0109] The method is basically the same as Example 2, except that: in step S3, the roller temperatures of the five-roll calender A and B rollers are set to 160°C, the roller temperature of the C roller is set to 120°C, the roller temperature of the D roller is set to 90°C, and the roller temperature of the E roller is set to 60°C; the gap between the A roller and the B roller is set to 0.80mm, the gap between the B roller and the C roller is set to 0.55mm, the gap between the C roller and the D roller is set to 0.45mm, and the gap between the D roller and the E roller is set to 0.40mm. The roller speed is set to 2.0m / min.
[0110] Table 1. Comparison of appearance and performance of the absorbing patches prepared in various embodiments of the present invention and comparative examples
[0111]
[0112]
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A Ka-band lightweight and high-strength absorbing patch, characterized in that: The absorbing patch comprises plastic particles, modified conductive absorber, stearic acid and additives; the plastic particles comprise polar plastic particles and non-polar plastic particles; the modified conductive absorber is a conductive absorber modified by a coupling agent; the conductive absorber comprises conductive carbon black and graphene.
2. The Ka-band lightweight and high-strength absorbing patch according to claim 1, characterized in that: The polar plastic particles account for 30-40% of the mass of the plastic particles; The amount of the conductive absorbent is 20-25% of the mass of the plastic particles; The amount of stearic acid used is 1-3% of the mass of the plastic particles; and / or The graphene accounts for 10% to 15% of the mass of the conductive absorbent.
3. The Ka-band lightweight and high-strength absorbing patch according to claim 1 or 2, characterized in that: The polar plastic particles include one or more of polyvinyl chloride, polyethylene terephthalate, and ethylene vinyl acetate; and / or The non-polar plastic particles include one or more of polyethylene, polypropylene, and polystyrene; preferably, the density of the non-polar plastic particles is 0.9 to 1.0 g / cm 3 .
4. The Ka-band lightweight and high-strength absorbing patch according to claim 1, characterized in that: The amount of the coupling agent is 1-10% of the mass of the conductive absorbent; preferably, the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
5. The Ka-band lightweight and high-strength absorbing patch according to claim 1, characterized in that: The dosage of the auxiliary agent is 0.5-1% of the mass of the plastic particles; preferably, the auxiliary agent is one or more of a mildew preventer, an anti-aging agent, an antibacterial agent, and an antioxidant.
6. The Ka-band lightweight and high-strength absorbing patch according to claim 1, characterized in that: The conductive carbon black has a particle size of 10 to 50 nm and an iodine adsorption value of 900 to 1500 mg / g; and / or The graphene is multilayer graphene; preferably, the number of layers of the multilayer graphene is 2 to 3.
7. A method for preparing the Ka-band lightweight and high-strength absorbing patch according to any one of claims 1 to 6, characterized in that: The preparation method comprises: The plastic particles, stearic acid, modified conductive absorbent and additives are mixed, and after a first banburying, an open banburying and a second banburying are performed to obtain a banburying mixture; The kneaded mixture is calendered by a five-roll calender to obtain a Ka-band lightweight and high-strength absorbing patch.
8. The preparation method according to claim 7, characterized in that: The first internal kneading is performed at a temperature of 100 to 150° C. and for a time of 60 to 80 minutes; The temperature of the open refining is 100-150°C and the time is 5-10 minutes; and / or The temperature of the second internal kneading is 100-150° C., and the time is 10-30 minutes.
9. The preparation method according to claim 7, characterized in that: The rotating speed of the internal mixer during the first internal mixing and the second internal mixing is 40-50 rpm / s; The linear speed of the mixing mill during the mixing process is 4 to 6 m / min; and / or During the calendering process, the roller speed of the calender is 1 to 1.5 m / min.
10. The preparation method according to claim 7, characterized in that: The five-roll calender comprises a first roller, a second roller, a third roller, a fourth roller and a fifth roller which are arranged in sequence from front to back; The roller temperature of the first roller is 140-150°C; the roller temperature of the second roller is 100-110°C; the roller temperature of the third roller is 100-110°C; the roller temperature of the fourth roller is 70-80°C; the roller temperature of the fifth roller is 40-50°C; The gap between the first roller and the second roller is 0.6-0.7 mm; the gap between the second roller and the third roller is 0.42-0.48 mm; the gap between the third roller and the fourth roller is 0.35-0.40 mm; the gap between the fourth roller and the fifth roller is 0.30-0.35 mm.